A framework for operationalizing risk: A practical approach to patient safety. Issue 1 (6th April 2018) - Mathews, Simon C.; Sutcliffe, Kathleen M.; Garrett, Margaret R.; Pronovost, Peter J.; Paine, Lori
Abstract: The importance of patient safety has grown tremendously; however, there are insufficient resources dedicated to its practical application. We provide an overview of the framework for addressing patient safety within the Johns Hopkins Health System, which approaches patient safety in the context of risk at the patient, provider, unit, and system levels. We present practical examples of how this approach is applied and highlight the resources needed as well as describe how it fits within the broader quality management infrastructure in the health system on its journey toward high reliability.